Divergent Total Syntheses to Azafluoranthene and Dehydroaporphine Alkaloids. Issue 28 (20th August 2015) - Khunnawutmanotham, Nisachon; Sahakitpichan, Poolsak; Chimnoi, Nitirat; Techasakul, Supanna
Abstract: Facile divergent total syntheses for azafluoranthene and dehydroaporphine alkaloids have been successfully developed. A common intermediate, a biarylsulfonamide‐protected amino aldehyde, underwent either a cascade or a stepwise cyclization to furnish a tetracyclic skeleton related to the azafluoranthene alkaloids. Natural products, triclisine and telitoxine, were prepared to illustrate the use of this approach. Subsequent C‐homologation of the aldehyde moiety on the same intermediate by means of a Wittig reaction allowed the synthesis of aporphine alkaloids, as exemplified by the preparation of dehydronornuciferine. This synthetic approach could be applicable to the syntheses of other azafluoranthene‐related as well as aporphine‐related alkaloids. Abstract : Facile divergent syntheses for azafluoranthene and dehydroaporphine alkaloids are reported by using a biarylsulfonamide‐protected amino aldehyde as a common intermediate. The natural azafluoranthenes, triclisine and telitoxine, and an aporphine alkaloid, dehydronornuciferine, were prepared to illustrate the use of this approach.